1996
DOI: 10.1113/jphysiol.1996.sp021610
|View full text |Cite
|
Sign up to set email alerts
|

Release properties of isolated neuromuscular boutons of the garter snake.

Abstract: 1. Motor nerve terminals innervating fibres in the transversus abdominis muscle of the garter snake comprise discrete boutons. Using a combination of enzymatic digestion and mechanical manipulation, individual boutons were removed from living terminals for study in isolation. 2. Boutons freed from terminals were usually allowed to remain in their original location on the endplate ('attached' one-bouton synapse). Alternatively, they were removed from the endplate, and then placed on the same or another vacant e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…3 as quantal content ( m = EPP/mEPP), with mean mEPP amplitude taken as 0.6 mV from prior experiments (). On average, ∼150 quanta were released initially from both normal and vesamicol‐treated terminals, consistent with previous estimates ( m = 1.4 quanta/bouton, 58 boutons/terminal; Wilkinson et al 1996). Removal of curare permitted the releasable pool's depletion time course to be assessed.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…3 as quantal content ( m = EPP/mEPP), with mean mEPP amplitude taken as 0.6 mV from prior experiments (). On average, ∼150 quanta were released initially from both normal and vesamicol‐treated terminals, consistent with previous estimates ( m = 1.4 quanta/bouton, 58 boutons/terminal; Wilkinson et al 1996). Removal of curare permitted the releasable pool's depletion time course to be assessed.…”
Section: Resultssupporting
confidence: 90%
“…The cut end of the central muscle's nerve was drawn into a suction electrode for stimulation with 200 µs negative‐going rectangular pulses of 2–7 V. Intracellular recording of endplate potentials (EPPs) and miniature endplate potentials (mEPPs) and subsequent analyses were performed using methods described elsewhere (Wilkinson et al 1992). Under these conditions, change in EPP amplitude reflects alteration in quantal content (Wilkinson et al 1996), not change in endplate sensitivity. Recording of mEPPs immediately after tetanic stimulation in separate experiments indicated that asynchronous transmitter release (which was not detected in curarized preparations and therefore ignored) accounted for 0.7% of total release, or less, in all experiments.…”
Section: Methodsmentioning
confidence: 99%
“…2C; r = 0·90; P < 0·001). Furthermore, calculations of quantal content per unit area (synaptic strength) ranged from less than 0·1 quanta ìm¦Â to about 1·4 quanta ìm¦Â, similar to the range reported in species as diverse as snakes and man (Slater et al 1992;Wilkinson et al 1996). The LPN-SN correlation coefficient for synaptic strength was less than that for normalised EPP amplitude but nevertheless highly significant ( Fig.…”
Section: Synaptic Strengths Of Convergent Inputs Were Co_regulatedmentioning
confidence: 87%
“…It is also possible to estimate the total number of endocytosed vesicles that was expected and compare this with the actual number that was found. Under low-frequency stimulus conditions similar to those that were used here, one snake motor bouton releases, on average, 1.4 quanta per stimulus ( Wilkinson et al, 1996). Thus ϳ210 quanta (vesicles) per bouton would have been released during our stimulus protocol, which should equal the number that was retrieved (Smith and Betz, 1996).…”
Section: Discussionmentioning
confidence: 99%